Overview of Nursing Care Implementation Critical in the Emergency Room of Santa Elisabeth Hospital Medan - Mestiana Br. Karo; Mardiati Barus; Brigitta Cahyani Silva Kristiani Waruwu (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
A Critical nursing care is a process for problem solving, decision making as well as an organized and systematic approach to nursing problems. Nursing care must be carried out completely and accurately because it is the nurse's self-defense against demands as well as proof that the correct nursing care has been carried out. The research objective is to find out the description of the implementation of critical nursing care in Emergency Room of Santa Elisabeth Hospital Medan 2023. The research design used is a descriptive research design. There are two populations in this study, namely nursing actions and documentation of critical nursing care, the sampling technique used purposive sampling 51 respondents and total sampling (critical nursing care documentation) as many as 68 respondents. The data collection instrument uses observation sheets for nursing actions consisting of infusions, ECG usage and oxygen therapy, as well as critical nursing care using observation sheets consisting of assessment, diagnosis, intervention/implementation and evaluation. The results show that the infusion was according to the SOP, the use of ECG was according to the SOP and sufficient oxygen therapy is according to the SOP for 51 respondents (100%). Critical nursing care complete review 65 (96%), diagnosis quite complete 48 (71%), complete intervention/implementation 65 (96%), complete evaluation 67 (99%) and documentation of critical nursing care majority complete 65 (96%) of 68 respondents. It is expected to be able to improve the accuracy and completeness of nursing care documentation through training for each officer.